Bidirectional relationship between visual spatial skill and Chinese character reading in Chinese kindergartners: A cross-lagged analysis - Lin, Dan; Sun, Huilin; Zhang, Xiao (Contemporary educational psychology, 2016)
•Reciprocal association between visual-spatial skills and Chinese character reading were found from K1 to K2.•The association of visual-spatial skills and Chinese character reading diminished from K2 to K3.•A developmental model on how visual-spatial skills is bidirectionally associated to Chinese reading were demonstrated. The current literature suggests mixed findings regarding the relationship between visual spatial skill and Chinese reading ability. In this longitudinal study, 106 kindergarteners in Hong Kong were tested on visual spatial skill and Chinese character reading ability in their first, second, and third years of kindergarten (K1, K2, and K3) with 12-month intervals between the three testing points. Cross-lagged path analysis showed a bidirectional relationship between visual spatial skill and Chinese character reading ability from K1 to K2. Children's visual spatial skill in K1 predicted their reading ability in K2 (B = 0.35, SE = 0.17, p < .05, β = .17), and their reading ability in K1 explained the unique variance of visual spatial skill measured in K2 (B = 0.29, SE = 0.12, p < .05, β = .25). In total, it explained 19.4% (p < .01) and 35.8% (p < .001) variance of visual spatial skill at T2 and reading ability at T2. However, the bidirectional relationship diminished between K2 and K3. The results demonstrate the developmental course of the relationship between visual spatial skill and reading ability as well as the reciprocal facilitation of the two skills in the beginning phase of reading development but not later phases.